2017
DOI: 10.1016/j.jcv.2017.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Detection and differentiation of HIV-2 using the point-of-care Alere q HIV-1/2 Detect nucleic acid test

Abstract: Background The Alere q HIV-1/-2 Detect test (Alere Detect) is a rapid point-of-care (POC) nucleic acid test (NAT) that can detect and differentiate HIV-1 and HIV-2 in 25-µL whole blood or plasma samples. The Alere Detect test has been validated for early infant diagnosis of HIV-1 infection, and it is the only POC NAT device currently known to detect HIV-2, which is endemic in West Africa. Objectives To evaluate the sensitivity detecting HIV-2 RNA and the differential performance of the Alere Detect. Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Chang et al . recently evaluated a new point‐of‐care molecular test for both HIV‐1 and HIV‐2 RNA quantification (Alere q HIV‐1/2 Detect; Alere Detect, Jena, Germany) and concluded that this test has potential for use in resource‐limited settings. For serological discrimination, the Geenius HIV 1/2 Supplementary Assay (Bio‐Rad, Marnes‐la‐Coquette, France ) has shown promising results , but further evaluation using samples from HIV‐1/2 dually infected patients is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al . recently evaluated a new point‐of‐care molecular test for both HIV‐1 and HIV‐2 RNA quantification (Alere q HIV‐1/2 Detect; Alere Detect, Jena, Germany) and concluded that this test has potential for use in resource‐limited settings. For serological discrimination, the Geenius HIV 1/2 Supplementary Assay (Bio‐Rad, Marnes‐la‐Coquette, France ) has shown promising results , but further evaluation using samples from HIV‐1/2 dually infected patients is needed.…”
Section: Discussionmentioning
confidence: 99%
“…For the development of a TFV-specific immunoassay ( Fig. 1 illustrates a schema of immunoassay development) [17] , the UCSF Hair Analytical Laboratory (HAL), with expertise in LC/MS–MS and analyzing ARV concentrations in hair in the context of HIV treatment and prevention [18] , [19] , formed a collaboration with Alere™ Rapid Diagnostics, a company with expertise in developing POC immunoassays [20] , [21] . Scientists from the UCSF HAL and Alere™ scrutinized the molecular structure of TFV to identify unique derivatives with structural distinction from endogenous nucleotides.…”
Section: Methodsmentioning
confidence: 99%
“…8, [98]). It is a fully automated platform for HIV-1 and HIV-2 detection within 50 min based on real-time PCR with multiplexing capability [99,100]. It is suitable for point-of-care use due to its portable nature, battery operation, no laptop requirement, easy to use touch screen, while the cartridge can be stored at room temperature without need for cold chain.…”
Section: Platform Description and Performance Of The Alere™ Qmentioning
confidence: 99%